DINAMIKA SISTEM UPACARA PERKAWINAN BATAK SIMALUNGUN DI KABUPATEN SIMALUNGUN, SUMATRA UTARA TAHUN 1950-2010 - Kurnia Sipayung, Frans (Humanis, 2015)
Simalungun is one of regencies in North Sumatra. This Study aims to determine the dynamics of the marital system of Batak Simalungun in 1950-2010. In addition, to find out the wedding ceremony of Batak Simalungun, understanding the influence of Christianity in the traditional wedding of Simalungun, as well as understanding the factors that cause people of Batak Simalungun to be less interested in the traditional wedding ceremony and also the people of Batak Simalungun wedding ceremony. To obtain the required data, the researchers used field research methods by using oral history techniques, techniques which aim to collect data by means of observation to learn about the site, interviews and documentation of traditional leaders of taking photos at weddings that still apply the tradition of Batak Simalungun. Literary study was done to collect the data by reading books related to the problem studied, documented the dynamics of the relationship of Batak Simalungun traditional wedding ceremonies.
Keywords: function, wedding, Batak Simalungun